Effect of analcite and exometabolites of fungus Penicillium roseopurpureum on the resistance of tomato to Fusarium and on microbiological and allelopathic properties of soil - Zaimenko, N.V.; Ellans’ka, N. E.; Didyk, N.P.; Yunoshev, O.P.; Yunosheva, O.P.; Ivanyts’ka, B.O.; Zakrasov, O.V.; Rositska, N.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
It is found that the treatment of tomato seeds with cultural medium of P. roseopurpureum and the application of analcite nanomaterial to soil increase the resistance to infestation by the phytopathogenes of Fusarium genus, significantly reduce the number of soil micromicetes (including pathogenes), improve the allelopathic, physical and chemical conditions of soil. The enhancement of the protective effect of analcite and cultural medium at their combined application is shown.